2006
DOI: 10.1097/01.mlg.0000231742.11048.ed
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly Cartilage Graft Inlay Tympanoplasty for Large Perforations

Abstract: Cartilage butterfly graft inlay tympanoplasty is effective in the vast majority of patients with moderate to large perforations. The closure rate exceeded 90% with no graft displacement, postoperative adverse events were respectably low, and hearing results improved or remained stable despite the need for concurrent mastoidectomy in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 15 publications
2
91
0
Order By: Relevance
“…6 The perceived disadvantage of the cartilage graft is that it creates an opaque tympanic membrane, which could potentially hide a residual cholesteatoma. 7 The results of our study were found to be comparable with other studies done by various authors. Neumann et al reported a graft take rate of 100% in their palisade cartilage tympanoplasty study, and they did not observe resorption or recurrent defects of the rebuilt tympanic membrane.…”
Section: Graft Used Take Up In % Hearing Results Khan Et Al [13]supporting
confidence: 83%
“…6 The perceived disadvantage of the cartilage graft is that it creates an opaque tympanic membrane, which could potentially hide a residual cholesteatoma. 7 The results of our study were found to be comparable with other studies done by various authors. Neumann et al reported a graft take rate of 100% in their palisade cartilage tympanoplasty study, and they did not observe resorption or recurrent defects of the rebuilt tympanic membrane.…”
Section: Graft Used Take Up In % Hearing Results Khan Et Al [13]supporting
confidence: 83%
“…For optimal acoustic transfer behaviour, the cartilage should be cut as thin as possible. The cartilage plates with the thickness of 0.5 mm show stiffness similar to that of healthy tympanic membrane and might be considered an acceptable compromise between satisfactory acoustic properties and sufficient mechanical stability [30]. In our study, Postoperative hearing was accessed 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of cartilage is high mechanical stability and long lasting vitality ever years after surgery. The success rate of ''take up'' by using cartilage grafts is reported up to 100% [24][25][26][27][28][29][30]. In our study, all the patients were followed up for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Couloigner V et al 6 assessed the results of cartilage tympanoplasty in 59 children and reported a 71% take rate compared to 83% take rate obtained with underlay fascia temporalis tympanoplasty. Hearing improvement was almost the same.…”
Section: Discussionmentioning
confidence: 99%